Interventional Techniques for Bone and Musculoskeletal Soft Tissue Tumors: Current Practices and Future Directions – Part II. Stabilization - Dalili, Danoob; Isaac, Amanda; Cazzato, Roberto Luigi; Åström, Gunnar; Bergh, Jonas; Mansour, Ramy; Weber, Marc-André; Garnon, Julien; Gangi, Afshin (Seminars in Musculoskeletal Radiology, 2020)
Percutaneous image-guided oncologic interventions have rapidly evolved over the last two decades as an independent strategy or used within a first-, second-, or even third-line strategy in the treatment of musculoskeletal (MSK) tumors. Abundant mostly nonrandomized publications have described the safety, efficacy, and reproducibility of implementing percutaneous therapies both with curative and palliative intent. In this article, we continue to share our experience in bone and MSK soft tissue interventions focusing on stabilization and combined ablation and stabilization. We propose a pathway and explore future directions of image-guided interventional oncology related to skeletal disease. We reflect on the advantages and limitations of each technique and offer guidance and pearls to improve outcomes. Representing patterns from our practices, we demonstrate the role of collaborative working within a multidisciplinary team, ideally within a dedicated tumor treatment center, to deliver patient-specific therapy plans that are value based and favored by patients when given the choice.
Keywords: interventional oncology; tumor; cementoplasty; stabilization; metastasis